Research Progress on Cenozoic Volcano Genesis and Fluid Action in Northeast China - Deng, Yufeng; Huang, Song; Wu, Xueshan; Li, Min (Frontiers in Earth Science, 2022)
The tectonic evolution of northeast China is closely related to the subduction of the Pacific plate. The dehydration of the slab subduction process produces metasomatic agents that have important effects on the physical and chemical properties of the mantle wedge, including the decrease of seismic wave velocity and the increase of Poisson’s ratio and electrical conductivity. In order to investigate the tectonic evolution and fluid action of northeast China, this paper compares the previous seismic and electromagnetic imaging results of northeast China and explores the relationship between the genesis of Cenozoic volcanoes and fluid action in northeast China through rheological analysis. The results show that the western Pacific plate subducted into the mantle transition zone beneath northeast China, and sustained dehydration occurred. The upward migration of these released water caused partial melting at the base of the upper mantle. Some of the upwelling streams pierced the weak tectonic boundary under the buoyancy effect, which finally formed the large-scale Cenozoic volcanic events in northeast China.